BUSINESS MODEL DESIGN AS A FORM OF STRATEGY BUSINESS DEVELOPMENT AT PT. PERUSAHAAN PERDAGANGAN INDONESIA (PERSERO) - Abu Hafs Al Faruq; Taufik Amir (Sean Institute, 2023)
Study This aim For Know overview of the business model at PT.Perusahaan Perdagangan Indonesia (Persero) if reviewed from aspects of the Business Model Canvas and for Know Development appropriate and recommended business _ For applied to PT. Perusahaan Perdagangan Indonesia (Persero). The type of research used by writer in study This is study Descriptive , Which aim For For know and be able explain variable yan researched in something situation . The data used in study This are primary and secondary data . Results in study This obtained renewal model business Which can applied by PT. Perusahaan Perdagangan Indonesia (Persero). Update There is in the block Activity Key , Source Main power and Structure Cost .